Perspektif Belajar dengan Seni Tari Tradisional di Sekolah Menengah Pertama - Wahyuni Syukur, Sri (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
This research aims to determine the perspective of learning with South Sulawesi Traditional Dance in Junior High Schools. This type of research uses qualitative research with an ethnographic approach. The subjects in this research were teachers and students at SMP Negeri 22 Bantimurung. The results of this research show that students who are already at the junior high school level have been equipped with sufficient knowledge to develop so that the learning process will be more challenging for teachers in order to increase students' interest and motivation to learn art in the classroom, one of which is by highlighting traditions and culture. Locally in the South Sulawesi area, namely the basic movements of South Sulawesi traditional dance. So, the role of arts education in junior high schools is an effort to improve students' abilities, especially in developing interests, increasing creative work, as well as knowing regional arts and the values ??contained therein. Through arts education, students are facilitated in the process of growth and development in three domains as learning outcomes, namely, cognitive, affective and psychomotor.